Peningkatan Motivasi untuk Melanjutkan Pendidikan Melalui Pengabdian Berbasis Service Learning di SMAN 8 Mataram - Muhamad Farhan Maulana; Inaz Putri Kamila; M. Sagos; Qomari Auliyah; Istiqomah Virginia; Ahmad Dani; Agus Kurnia (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
Quality education is one of the important sustainable development goals in the progress of a region. Statistical data shows that the participation rate of 7-24 years old in Mataram City in higher education is 12.99%. This figure is still far below the national gross participation rate that continues to higher education, which is 31.45%. To increase students' motivation in continuing their education, role models are needed for them to share their experiences. Therefore, this activity aims to support efforts to improve the quality of inclusive and equitable education in Mataram City to ensure lifelong learning opportunities for all students and motivate them to continue to higher education. This service program is carried out with a service learning approach through counseling, training, and mentoring to students at SMAN 8 Mataram. The implementation method includes several stages, namely: preparation of materials, inclusive learning implementation training and introduction of learning technology for students to encourage independent and collaborative learning. The results of this activity show an increase in students' understanding of the concept of inclusive education as well as an increase in student motivation to participate in lifelong learning activities.